2021
DOI: 10.1049/nbt2.12039
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicity of as‐synthesised copper nanoparticles on soil bacteria

Abstract: Release of metallic nanoparticles in soil poses a serious threat to the ecosystem as they can affect the soil properties and impose toxicity on soil microbes that are involved in the biogeochemical cycling. In this work, in vitro ecotoxicity of as-synthesised copper nanoparticles (CuNPs) on Bacillus subtilis (MTCC No. 441) and Pseudomonas fluorescens (MTCC No. 1749), which are commonly present in soil was investigated. Three sets of colloidal CuNPs with identical physical properties were synthesised by chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Sharma et al have also reported similar results for gram-negative Pseudomonas fluorescens and gram-positive B. subtilis exposed to copper nanoparticles. The authors observed a decrease in the ROS level above MICs and suggested that the reason for cell death was caused by higher oxidative stress at minimal bactericidal concentrations 65 . The maximum ROS intensity induced by MIT was 4.93 times higher than that of the biotic control and was observed in S. mali at 7.813 mg L −1 MIT.…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 99%
“…Sharma et al have also reported similar results for gram-negative Pseudomonas fluorescens and gram-positive B. subtilis exposed to copper nanoparticles. The authors observed a decrease in the ROS level above MICs and suggested that the reason for cell death was caused by higher oxidative stress at minimal bactericidal concentrations 65 . The maximum ROS intensity induced by MIT was 4.93 times higher than that of the biotic control and was observed in S. mali at 7.813 mg L −1 MIT.…”
Section: Inhibition Of Biofilm Formationmentioning
confidence: 99%
“…7 The size of CuO-NPs also plays a crucial role in their toxicity; smaller nanoparticles often exhibit greater toxicity due to their increased surface area and reactivity. 8 Additionally, the accumulation of nano-Cu particles in various organs is reported. 9 Excessive ROS production may disrupt cells' antioxidant defense mechanisms, leading to OS, inflammation, and ultimately cellular damage.…”
Section: Introductionmentioning
confidence: 99%
“…7 The size of CuO-NPs also plays a crucial role in their toxicity; smaller nanoparticles often exhibit greater toxicity due to their increased surface area and reactivity. 8…”
Section: Introductionmentioning
confidence: 99%